Exploring Resilience and Spirituality among Recovery Drug Addicts in Drug Rehabilitation Center - Mohamad Yasin, Nurhafizah; Shafie, Amin Al Haadi; Baharudin, Dini Farhana (International Journal of Pedagogy and Learning Community (IJPLC), 2024)
Research has shown that lack in resilience may contribute to relapse among former drug addicts. Furthermore, spirituality is recognized as a factor that can positively influence resilience levels. This study investigates the connection between resilience and spirituality among individuals undergoing treatment in drug rehabilitation centres. The objectives were to assess: (1) the level of spirituality among drug addicts, (2) the level of resilience among drug addicts, and (3) the correlation between spirituality and resilience. Using a correlational research design and quantitative methodology, data were collected from 224 participants who are inmate from drug rehabilitation centre. The Connor-Davidson Resilience Scale (CD-RISC) and the Ummatic Personality Inventory (UPI) were utilized to measure resilience and spirituality, respectively. Results indicated that most participants demonstrated moderate levels of spirituality (75%) and resilience (62.5%). A significant positive relationship between the two variables was found (Pearson’s r = 0.665, p < 0.001), indicating that higher levels of spirituality are associated with increased resilience among drug addicts in rehabilitation.